Pengaruh Laverage, Earning Power dan Net Profit Margin Terhadap Manajemen Laba pada Perusahaan Property dan Real Estate yang Terdaftar di BEI Tahun 2019-2023 - Fitri Nur Kaifa; Mulyadi Mulyadi; Elia Rossa (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This research uses a quantitative approach to analyze the effect of leverage, earning power, and net profit margin on profit management in Property and Real Estate companies listed on the Indonesia Stock Exchange in 2019-2023. The population of this study consists of 92 companies listed in the Property and Real Estate index during 2019-2023, with a sample of 85 data. The results show that leverage has a negative effect on profit management, while earning power (EP) and net profit margin (NPM) have a positive effect on profit management. Keywords: , , , , .